Quasilinear elliptic systems of resonant type and nonlinear eigenvalue problems - De Napoli, P.L. (2002)
This work is devoted to the study of a quasilinear elliptic system of resonant type. We prove the existence of infinitely many solutions of a related nonlinear eigenvalue problem. Applying an abstract minimax theorem, we obtain a solution of the quasilinear system -Δ pu = F u(x,u,v), -Δ qv = F v(x,u,v), under conditions involving the first and the second eigenvalues. Copyright © 2002 Hindawi Publishing Corporation.